EFFECTIVENESS OF MICROBIOLOGICAL PRODUCTS AGAINST PEROMONOUS TRANSMISSION IN APPLE FRUIT IN ORCHARDS - M. K. Raxmonova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Research is being conducted on advanced technologies for growing agricultural products and protecting them from pests and diseases in order to ensure food security in the world and gain a foothold in the world market. However, the fact that some of the products grown in orchards are still destroyed by the apple orchard (Carpocapsa pomonella L.) requires the improvement of this pest control system.